Performance of Three-Parameters Dirichlet Universal Portfolio During COVID-19 Pandemic - Yeok Qin, Goh; Sook Theng, Pang (Enthusiastic : International Journal of Applied Statistics and Data Science, 2024)
Stock returns are often the primary objectives for investors, financial analysts as well as the politicians with the intention to make a right investment decision. In this paper, we study the performance of the three-parameters Dirichlet universal portfolio on selected stocks during the COVID-19 pandemic. Some empirical results are obtained based on some selected data sets from the local stock exchange. The period of trading of the stocks are selected from 2nd January 2020 to 18th August 2021 consisting of 400 trading days. The empirical results seem to indicate the three-parameters Dirichlet universal portfolio performs well during the COVID-19 pandemic by a proper choice of parameters. Also, this study provides evidence that the capital achievement at the end of the 400th trading days is influenced by the arrangement of the stocks within each selected data set. Besides, the performance of the homogeneous datasets, particularly, main data set from healthcare sector, is better than heterogeneous datasets during the COVID-19 pandemic.